Pain in German physiotherapists: an analysis of pain prevalence and analgesics intake - Steiner, Sarah; Möckel, Luis (physioscience, 2021)
Background Healthcare professionals of different occupations report pain, in particular back pain. It is known that the handling of patients and standing for long periods of time – like physiotherapists do, as well as working in bent posture – are causes of back pain. A high prevalence of low back pain (LBP) in German physiotherapists is to be expected.Objective To determine pain point prevalence, severity of pain, type of pain (acute, chronic, recurrent), most affected body locations and extent of analgesics intake in German physiotherapists.Method This was a nationwide online survey with German physiotherapists. Univariable and multivariable methods were applied to identify associations between sociodemographic variables and pain, type of pain and pain location as well as analgesic intake by type of pain. In addition, severity of pain by type was examined using the Kruska-Wallis Test.Results A total of 550 physiotherapists were included in the analysis. Prevalence of pain was 63.09 % (acute: 4.18 %, chronic: 15.27 %, recurrent: 43.64 %). Most frequently mentioned pain locations were lumbar spine (49.27 %), cervical spine (48.39 %) and head (40.47 %). Participants with chronic pain reported a higher pain severity than physiotherapists with recurrent pain. Analgesics were used by 35.29 % of study participants with pain. Participants with chronic pain indicated a significantly higher probability of using analgesics compared to physiotherapists with recurrent pain.Conclusion This study indicates a high prevalence of pain and analgesics intake in participating physiotherapists. Therefore, measures are needed to reduce pain in German physiotherapists.
Keywords: work-related disorders; musculoskeletal disorders; occupational medicine; pain relievers